(untitled) (Academicia Globe: Inderscience Research, 2023)
The human body lives and replenishes its energy needs at the expense of nutrients in consumer products: proteins, fats, carbohydrates, water, mineral salts, vitamins and other substances. Life processes depend on proteins and their biological function. Irrational protein nutrition is used for two purposes. Firstly, to lose excess weight, and secondly, in pathological conditions (hypotrophy, chronic diseases and athletes) to strengthen the general condition of the patient and increased body weight. In this experiment, the effect of irrational protein nutrition on body weight in experimental animals was studied.